2013
DOI: 10.1109/jlt.2013.2267891
|View full text |Cite
|
Sign up to set email alerts
|

Optical Image Encryption Based on Chaotic Baker Map and Double Random Phase Encoding

Abstract: This paper presents a new technique for optical image encryption based on chaotic Baker map and Double Random Phase Encoding (DRPE). This technique is implemented in two layers to enhance the security level of the classical DRPE. The first layer is a pre-processing layer, which is performed with the chaotic Baker map on the original image. In the second layer, the classical DRPE is utilized. Matlab simulation experiments show that the proposed technique enhances the security level of the DRPE, and at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…Chaotic encryption schemes are provided superior level of security than conventional ciphers [34]. A chaotic system is also used with ECG signal to provide higher speed and security with encryption [35].…”
Section: E Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaotic encryption schemes are provided superior level of security than conventional ciphers [34]. A chaotic system is also used with ECG signal to provide higher speed and security with encryption [35].…”
Section: E Motivationmentioning
confidence: 99%
“…Logistic map has high potential to be used to design a stream cipher for real-time embedded systems [37], [38]. Fu's chaotic cipher is secure and the information leak of chaos map is discovered [39].…”
Section: E Motivationmentioning
confidence: 99%
“…However, Kumar et al [34] have demonstrated the vulnerability of (DRPAE) scheme in front of a point spread function attack and He et al [33] have proved that DRPAE is also vulnerable to a Hybrid two-step attack, which utilizes a chosen-plaintext attack followed by a known-plaintext attack. Recently, Elshamy et al [45] proposed an optical image encryption method based on chaotic Baker map and DRPE, which consists of two layers. The first layer is a preprocessing chaotic baker map which performs the randomization of the image pixels and the second layer is the conventional DRPE.…”
Section: Introductionmentioning
confidence: 99%
“…Encryption has several applications in Internet communication, multimedia systems, medical imaging, telemedicine, military communication, pay-TV, and confidential video conferencing, etc. In this regard, a variety of encryption schemes have been proposed to mask the multimedia data streams, such as DES (Data Encryption Standard) [1][2], optical encryption [3][4][5][6][7], IDEA (International Data Encryption Algorithm) [8][9] and RSA [9].…”
Section: Introductionmentioning
confidence: 99%